Predictors of Mortality among Patients Lost to Follow up Antiretroviral Therapy - Putu Dian Prima Kusuma Dewi; Gede Budi Widiarta (Universitas Airlangga, 2018)
Introduction: The death of HIV/AIDS patients after receiving therapy in Bali is the seventh highest percentage of deaths in Indonesia. LTFU increases the risk of death in PLHA, given the saturation of people with HIV taking medication. The level of consistency in the treatment is very important to maintain the resilience and quality of life of people living with HIV. This study aims to determine the incidence rate, median time and predictors of death occurring in LTFU patients as seen from their sociodemographic and clinical characteristics. Methods: This study used an analytical longitudinal approach with retrospective secondary data analysis in a cohort of HIV-positive patients receiving ARV therapy at the Buleleng District Hospital in the period 2006-2015. The study used the survival analysis available within the STATA SE 12 software Results: The result showed that the incidence rate of death in LTFU patients was 65.9 per 100 persons, with the median time occurrence of 0.2 years (2.53 months). The NNRTI-class antiretroviral evapirens agents were shown to increase the risk of incidence of death in LTFU patients 3.92 times greater than the nevirapine group (HR 3.92; p = 0.007 (CI 1.46-10.51). Each 1 kg increase in body weight decreased the risk of death in LTFU patients by 6% (HR 0.94; p = 0.035 (CI 0.89-0.99). Conclusion: An evaluation and the monitoring of patient tracking with LTFU should be undertaken to improve sustainability. Furthermore, an observation of the LTFU patient's final condition with primary data and qualitative research needs to be done so then it can explore more deeply the reasons behind LTFU.